To Examine The Possible Impact Of Gst In Msmes In Haryana (Journal of Namibian Studies : History Politics Culture, 2023)
Micro, small, and medium-sized enterprises (MSMEs) in India were hit hard by the Goods and Services Tax (GST). The goals of this tax overhaul were to simplify indirect taxation, strengthen the single market, and facilitate corporate operations. Its positive and negative effects on MSMEs reflect the complexity of the terrain in which they operate. The streamlining of taxes processes was one of the most noticeable advantages of GST for MSMEs. To make things easier for companies, GST took the role of several other state and federal taxes. As a result, tax collection efficiencies increased and tax avoidance decreased. Businesses were able to more easily report their tax payments because to the GST network's electronic filing and credit claim system. However, many SMEs had problems with the introduction of GST. Companies' resources were stretched thin as they struggled to adjust to the additional compliance demands brought on by the switch to a different tax system. The high compliance costs for small businesses were a direct result of the complexity of the tax system. GST's effect on MSMEs' competitiveness was industry specific. The tax costs on certain small and medium-sized businesses were cut while others were increased. Cost structures were affected by the possibility of receiving an input tax credit, with the greatest advantages accruing to companies involved in manufacturing and value addition. The dynamics of SMEs' supply chains were also impacted by GST. As a result, more companies began giving preference to vendors who were GST-compliant. As a result, many formerly informal businesses registered for GST. However, it also meant facing tougher competition from established powerhouses. For micro, small, and medium-sized enterprises (MSMEs), the effects of GST were complicated. While its ultimate goals were to streamline taxes and increase formalisation, its implementation first disrupted many small firms and made it difficult for them to comply. Factors include sector-specific dynamics and the adaptability of MSMEs to the new tax system will determine the long-term consequences. The effects of the changing and adapting GST on MSMEs have been the topic of continuing research and discussion.